Urban Transport Systems - Yaghoubi, Hamid (IntechOpen, 2017)
This book contains a collection of latest research developments on the urban transportation systems. It describes rail transit systems, subways, bus rapid transit (BRT) systems, taxicabs, automobiles, etc. This book also studies the technical parameters and provides a comprehensive overview of the significant characteristics for urban transportation systems, including energy management systems, wireless communication systems, operations and maintenance systems, transport serviceability, environmental problems and solutions, simulation, modelling, analysis, design, safety and risk, standards, traffic congestion, ride quality, air quality, noise and vibration, financial and economic aspects, pricing strategies, etc. This professional book as a credible source can be very applicable and useful for all professors, researchers, students, experienced technical professionals, practitioners and others interested in urban transportation systems.